2021
DOI: 10.1055/s-0041-1735134
|View full text |Cite
|
Sign up to set email alerts
|

Creating Clarity in Noisy Environments by Using Deep Learning in Hearing Aids

Abstract: Hearing aids continue to acquire increasingly sophisticated sound-processing features beyond basic amplification. On the one hand, these have the potential to add user benefit and allow for personalization. On the other hand, if such features are to benefit according to their potential, they require clinicians to be acquainted with both the underlying technologies and the specific fitting handles made available by the individual hearing aid manufacturers. Ensuring benefit from hearing aids in typical daily lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…While we do not test for it here, we also expect improvements in cognitive load with our system, considering that it increases the effective SNR of noisy sounds by up to 16 dB 45 . In contrast to studies using traditional denoising algorithms, a recent study has shown that deep learning based denoising 23 on hearing aids can improve speech intelligibility for hearing impaired subjects. Our work is in line with other research in this field 16 18 and shows the improvements to speech intelligibility that can be made with more powerful neural network models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we do not test for it here, we also expect improvements in cognitive load with our system, considering that it increases the effective SNR of noisy sounds by up to 16 dB 45 . In contrast to studies using traditional denoising algorithms, a recent study has shown that deep learning based denoising 23 on hearing aids can improve speech intelligibility for hearing impaired subjects. Our work is in line with other research in this field 16 18 and shows the improvements to speech intelligibility that can be made with more powerful neural network models.…”
Section: Discussionmentioning
confidence: 99%
“…For the majority of hearing aid users, with less severe hearing loss 22 , it is more challenging to provide intelligibility improvements through denoising. A very recent study has shown the ability of a deep learning based denoising system to moderately improve speech intelligibility for hearing aid users 23 . Our work builds upon these exciting results and demonstrates that deep learning based denoising may be used to provide large improvements in speech intelligibility for hearing aid users in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Further research might also examine performance in conditions in which the beamformer is not optimised for the true target position, since this optimisation may limit the potential for mask-informed enhancement to provide additional benefit. Finally, it would also be of interest to compare the performance of the processing methods used here to that of other approaches to integrating spatial filtering and speech enhancement (e.g., Andersen et al, 2021;Koutrouvelis, Hendriks, Heusdens & Jensen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These include the potential for bilateral HAs to exchange information and the use of deep neural networks (DNNs) to aid the separation of speech from noise (e.g., Kolbaek, Yu, Tan & Jensen, 2017;Luo & Mesgarani, 2019;Xu, Du, Dai & Lee, 2015). A major focus of current research concerns how to integrate techniques such as spatial filtering and speech enhancement (e.g., Andersen et al, 2021;Koutrouvelis, Hendriks, Heusdens & Jensen, 2017). The ultimate goal is to raise the signal-to-noise-ratio (SNR) of target speech as much as possible while maintaining sufficient flexibility to accommodate changes in the target source and preserving a natural seeming sound environment, including spatial information.…”
Section: Introductionmentioning
confidence: 99%
“…However, individuals with a sensorineural hearing loss often experience great difficulties in understanding speech in noisy environments (Kochkin, 2000), also referred to as “supra-threshold distortion”, which is not necessarily well predicted from pure-tone audiometry (Vermiglio and Fang, 2022) and which amplification alone does not solve (Plomp, 1978; Grant et al, 2013). Most of today’s state-of-the-art hearing aids have the ability to improve speech understanding in challenging speech-in-noise situations, but the need for optimal fitting of these sound-processing features vary greatly among individuals (Andersen et al, 2021; Zaar et al, 2023b). To fit the hearing aids such that each patient’s individual needs are met, the clinician needs information about the degree to which the patient is struggling in real life speech-in-noise scenarios, when audibility is compensated for.…”
Section: Introductionmentioning
confidence: 99%